Integrating Spirituality, Culture, and Technology through a Living Curriculum in Islamic Religious Education at Islamic Boarding Schools - Nafsiyah; Nizar Albakhar; Saiful Yamin; Mochamad Iskarim (Jurnal Praktik Baik Pembelajaran Sekolah dan Pesantren, 2026)
The Living Islamic Religious Education Curriculum (Pendidikan Agama Islam/PAI) represents an educational paradigm that emphasizes the internalization and sustainability of Islamic values within students’ everyday lives. Central to this approach is the integration of spirituality, culture, and technology, which expands the scope of Islamic education beyond knowledge transmission toward character formation and personal transformation. This synergistic integration enables students to develop religious identities that are rooted in local cultural contexts while remaining responsive and competitive in a globalized environment, particularly within Islamic boarding school settings. Al Otsmani Islamic Boarding School serves as a representative case of this integrated curriculum implementation. The institution aligns its curriculum with the National Education Calendar, adapts learning materials to students’ contextual needs, and equips learners with both religious knowledge and essential soft skills. This study employs a qualitative research approach, utilizing descriptive data collected through observations and in-depth interviews. Such methods allow for a comprehensive exploration of curriculum practices and their lived implementation within the boarding school environment. The findings reveal that Al Otsmani Islamic Boarding School has undergone a significant educational transformation by integrating spiritual values across formal and traditional learning systems. This integration reflects the core principles of the PAI Living Curriculum, emphasizing the relevance of local culture and the practical application of Islamic values in students’ daily lives. Overall, the study highlights the potential of the Living PAI Curriculum as a holistic educational model that fosters spiritual depth, cultural awareness, and adaptive competencies in contemporary Islamic education contexts.